Application of Plasmid Engineering to Enhance Yield and Quality of Plasmid for Vaccine and Gene Therapy - Olusegun Folarin; Darren Nesbeth; John M. Ward; Eli Keshavarz-Moore (Bioengineering, 2019)
There is an increased interest in plasmid DNA as therapeutics. This is evident in the number of ongoing clinical trials involving the use of plasmid DNA. In order to be an effective therapeutic, high yield and high level of supercoiling are required. From the bioprocessing point of view, the supercoiling level potentially has an impact on the ease of downstream processing. We approached meeting these requirements through plasmid engineering. A 7.2 kb plasmid was developed by the insertion of a bacteriophage Mu strong gyrase-binding sequence (Mu-SGS) to a 6.8 kb pSVβ-Gal and it was used to transform four different E. coli strains, and cultured in order to investigate the Mu-SGS effect and dependence on strain. There was an increase of over 20% in the total plasmid yield with pSVβ-Gal398 in two of the strains. The supercoiled topoisomer content was increased by 5% in both strains leading to a 27% increase in the overall yield. The extent of supercoiling was examined using superhelical density (σ) quantification with pSVβ-Gal398 maintaining a superhelical density of −0.022, and pSVβ-Gal −0.019, in both strains. This study has shown that plasmid modification with the Mu-phage SGS sequence has a beneficial effect on improving not only the yield of total plasmid but also the supercoiled topoisomer content of therapeutic plasmid DNA during bioprocessing.